Multimodality of a press text, or about the relationship between word and image. A case study of Justyna Kopińska’s documentary Oddział chorych ze strachu and graphic artwork by Anna Reinert - Ślawska, Magdalena (Papers in Linguistics, 2020)
This article attempts to describe the relationship between word and image in a press text. It is a case study, i.e. an analysis of a documentary by Justyna Kopińska entitled Oddział chorych ze strachu [Ward for the Sick with Fear] and the accompanying graphic artwork by Anna Reinert. The use of research tools typical of media and language research made it possible to undertake a multimodal analysis of the text. From the sender’s perspective, the text is based on two textual strategies. The first is extratextual, pragmatic, one in which the relationship between word and image is paratextual, and which constitutes a preview of the main text of the documentary. The second, in-text strategy is realized on the compositional layer, while graphics and the text of the documentary are integrated within the page layout. The article also presents the reception of the text and the graphics as reported in a scientific experiment, in which students of journalism and social communication at the University of Silesia took part.